USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING PHYSICS IN PEDAGOGICAL UNIVERSITIES - Yulduz Xayrulloqizi Xudoyberdiyeva (Journal Park Publishing, 2023)
The article talks about the use of information communication technologies in teaching physics. It is necessary to use information technologies to increase the effectiveness of the lesson. In order to improve the quality of education, it is suggested to hold classes using information and communication tools.
Keywords: Information technology, Physics, educational quality, educational efficiency, educational methods.